Positron annihilation in alkali-halide crystals after electron irradiation - Vorobyev А. А. Alexander Akimovich (1974, 1974)
The effect of electron beam irradiation on the positron annihilation in KCl, KBr, NaCl single crystals was investigated. The narrowing of the angular correlation curves increases up to the saturation value with the absorbed radiation dose. The shape of the received narrow components differs from the narrow component measured in the additively colored samples. This phenomenon shows the considerable influence of the hole centres upon the positron annihilation in ionic crystals.